ULTRASTRUCTURAL ORGANIZATION OF THE PINEAL GLAND - Ravshanova Sevinch Azamat qizi; Soibnazarova Malika Xamidjan qizi; Qoraboyeva Mehri Xayitboyevna; Ruzimurodova Shahzoda Shavkat qizi (Modern American Journals, 2025)
Ravshanova Sevinch Azamat qizi